Etika Bisnis Islam Dan Kelangsungan Usaha Aqiqah Service Centre (ASC) Di Gresik - Misbahul Khoir; Moh. Ah. Subhan ZA (Universitas Islam Lamongan, 2019)
The idea of this research comes from the experience of researchers who, since married two years ago, is faced with a family environment that grows up and carries on their lives for generations through Aqiqah businesses service. The Aqiqah Service Center (ASC) is the first and oldest aqiqah service center in Gresik because it has been more than 50 years and has contributed to the formation of an Islamic generation by serving, assisting, and facilitating the intentions of Muslim parents in the city of students in Gresik and its surroundings in making goats goat for their children. The research will answer two questions: (1) What is the difference between Islamic business ethics and non-Islamic business ethics, and (2) How is the urgency of Islamic business ethics in the business continuity of the Aqiqah Service Center (ASC) in Gresik? This study is a qualitative-descriptive study with the aim of understanding the phenomena experienced by the subject of research including behavior, perception, motivation, and action holistically by utilizing various scientific methods. Data collection methods include; observation, in-depth interview or focus group discussion, and documentation. Data analysis techniques include: processing and preparing data for analysis, reading the entire data, analyzing in more detail by coding data, considering detailed instructions that can help the coding process, giving descriptions that will be presented in the report, interpreting and interpreting data. The result of research shows that The difference between islamic business ethics and conventional is in terms of; sources, motives, paradigms, foundations and basic foundations. The business of the ASC (Aqiqah Service Center) UD. H. M. Arba'i in Gresik, besides looking for qi>mah ma>diyyah (material value), but also must be able to obtain and give two other orientations, namely qi>mah khulu>qiyyah and qi>mah ru>hiyyah. Qi>mah khulu>qiyyah is a noble moral value which becomes a necessity that arises in business activities, so as to create an Islamic fraternity, between business managers and employees, as well as between sellers and buyers. Qi>mah ru>hiyyah means, the business act is intended to get closer to Allah SWT. In other words, when carrying out a business activity, it must be accompanied by an awareness of the relationship with God. This is what is meant, that every Muslim act is worship. Charity worship is material, while awareness of the relationship with God when doing business is called the spirit. Keywords: Islamic business ethics, Aqiqah Service Centre